-الفاظ المصائب والشدائد العامة في الذكر الحكيم-دراسة دلالية - د.صلاح الدين سليم محمد احمد العبادي (University of Mosul-college of Basic Education, 2024)
كشف البحث دلالة ألفاظ المصائب والشدائد العامة في الذكر الحكيم عبر استقراء الألفاظ والتراكيب في الآيات القرآنية الكريمة.وبين البحث الفروق والظلال الدلالية الدقيقة بين الألفاظ والتراكيب، ومحال أن يختلف لفظان والمعنى واحد في الذكر الحكيم؛ لأنَّ لغة القرآن اجتمعت فيه منابع الفصاحة بحكمة بالغة وأنها مختارة من لدن العزيز الحكيم.وقُسم البحث على محورين تناول الأول دلالة المصيبة في الذكر الحكيم، وكشف الثاني دلالة ألفاظ المصائب والشدائد العامة.The research revealed the significance of the words of general calamities and hardships in the Holy Quran by extrapolating the words and structures in the Holy Qur’anic versesThe research showed the subtle differences and semantic shades between words and structures, and it is impossible for two words to differ while the meaning is the same in the Holy Quran. Because the language of the Qur’an contains the sources of eloquence with great wisdom and it was chosen by the Mighty, the Wise.The research was divided into two parts. The first dealt with the significance of calamity in the Holy Quran, and the second revealed the significance of the words of calamities and general adversity